Proceedings of the Twelfth International Workshop on Multimedia Data Mining 2012
DOI: 10.1145/2343862.2343866
|View full text |Cite
|
Sign up to set email alerts
|

The impact of images on user clicks in product search

Abstract: Product search engine faces unique challenges that differ from web page search. The goal of a product search engine is to rank relevant items that the user may be interested in purchasing. Clicks provide a strong signal of a user's interest in an item. Traditional click prediction models include many features such as document text, price, and user information. In this paper, we propose adding information extracted from the thumbnail image of the item as additional features for click prediction. Specifically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Image Quality in Online Marketplaces. Previous work has shown that image-based features such as brightness, contrast, and background lightness contribute to the prediction of click-through rate (CTR) in the context of product search [5,11]. This line of work used hand-crafted image features, but did not actually assess the image quality as dependent variable.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Image Quality in Online Marketplaces. Previous work has shown that image-based features such as brightness, contrast, and background lightness contribute to the prediction of click-through rate (CTR) in the context of product search [5,11]. This line of work used hand-crafted image features, but did not actually assess the image quality as dependent variable.…”
Section: Related Workmentioning
confidence: 99%
“…In this work, we leverage our annotated dataset, and conducted the first computational analysis of the impact of common product photography tips on image quality. Unlike previous work [5,11] that analyzed the impact of image features on clicks, we evaluate directly on potential buyers' perception of image quality. In a later section, we then show how image quality can in turn predict sales outcomes.…”
Section: What Makes a Good Product Photo?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study showed that certain image features can also help to improve click through rate in product search engine [11,7]. The authors conducted experiments to show that including image features in a machine learned click based ranking model improves the NDCG (normalized discounted cumulative gain) of the search results.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Because some of the these features are computed from RGB values (0-255), as a convention, the range of quality score is also kept in [0, 255], whereas a score of 255 means the best quality. Potential readers are referred to [7,11] for details.…”
Section: Image Qualitymentioning
confidence: 99%